The Effect of Variation of Palm Fronds Absorbent Concentration In Adsorption Process to Reduce Free Fatty Acid Content on Tengkawang Oil - Puspita, Filda Agum; Oktaviani, Eva Pramuni; Rakasiwi, Rinjani Ratih; Ivontianti, Wivina Diah (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2023)
Tengkawang oil that hasn’t through purification process contains free fatty acid that can affect its quality, where this essence is the polluter that must be removed because it can caused a rancid. The removal of free fatty acid content on Tengkawang oil was done through adsorption process utilizing palm fronds adsorbent by using its cellulose content. Palm fronds went through dilegnification process using 10% of NaOH, then adsorption process was conducted with adsorbent concentration variety 5, 10, 15, 20 and 25%. Adsorbent characterized by utilizing FTIR and SAA, from FTIR result shows that palm fronds contain berlignocellulose function cluster, after delignification the C=C lignin compound function cluster still can be found on FTIR result and after adsorption O-H cluster went through intensity decrement which shows that cellulose content and hydroxyl (-OH) cluster reacted with adsorbat. Furthermore, there’s absorption on C-H function cluster that indicates the existence of free fatty acid compound and other polluter that adsorbed by palm fronds adsorbent. The characteristic of palm fronds adsorbent after delignification process was conducted shows the pore size is on micropore range with surface area of 6.480 m2/g, pore volume of 0.01138 cc/g and pore radius of 12.4 Å. The result of the research shows decreasing percentage of free fatty acid, capacity value and adsorption effectiveness of Tengkawang oil that the highest is on adsorbent concentration as much as 25% with decreasing percentage of free fatty acid as much as 4.68%, adsorption capacity as much as 207.19 mg/g and adsorption effectiveness as much as 36.28%. Keywords: adsorption; delignification; free fatty acid; tengkawang oil